Implementasi Keuangan Publik Islam (Studi Pada Kriterium Kaya Dalam Zakat Terhadap Perda Zakat Di Sulawesi Selatan) - Mustafa Darwis; Abdul Rahim (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This study is a study of the criteria that are rich in the zakat profession in Regional Regulations in South Sulawesi. Rich Criterium is a benchmark used by syara 'in establishing zalcat mali's obligation to muzakki. As is the case with professional charities as one part of zakat. The subject is how the criteria are rich in the Zakat Profession, with the sub-subject determining the criteria for rich wealth and wealth of rich zakat as syar'i considerations in the zakat profession in South Sulawesi. This problem is analyzed using the normative theological approach and normative juridical approach, by processing qualitative data, and analyzing data in the form of content analysis. Determination of the criteria for rich in wealth charity (māl) is a syara decision, only in jurisprudential terms known as 'compulsory zakat requirements', which basically requires zakat only for the rich. There are three indicators that function as criteria for wealth, namely profit from needs and free of debt, productive property, and niṣāb. Therefore, the criteria for richness must be one of the syar'i's considerations in determining the profession of zakat which is regulated in the zakat regulation in South Sulawesi. The rich criteria referred to are the ni adalahāb gold union of 20 miṡqāl and removed from net income (net), so that the actual zakat issued is an excess of basic needs